Does kangaroo mother care have an impact on morbidity, mortality and duration of hospital stay of newly born low birth weight babies? - Margekar, Purnima; Parekh, Premlata; Margekar, Shubha Laxmi (International Journal of Contemporary Pediatrics, 2021)
Background: Preterm and low birth weight infants are more likely to experience neonatal morbidity including acute respiratory, gastrointestinal, central nervous system, immunologic, hearing and vision problems than both term and normal weight infants who survive the neonatal period. The present study was aimed to evaluate the impact of Kangaroo Mother Care (KMC) on morbidity and mortality of new-borns and duration of hospital stay. Methods: A prospective case control study over a 12 month period was conducted from August 2013 to August 2014 on 50 new-borns weighing less than 1.8 kg. The primary outcome variable was “weight gain”. Secondary measures included morbidity, mortality and duration of hospitalization. Observations were recorded in a proforma specially designed for the study. The results were subjected to statistical analysis. Results: The hospital stay was less amongst neonates who received KMC. Twenty four (48%) out of 50 were discharged within 10 days, another 24 within 11 to 20 days. Neonates who did not received KMC, majority i.e. 27 of the neonates were in the ICU for 11-20 days. There were 3 neonates who stayed beyond 1 month. Conclusions: The study showed that KMC is useful method of caring VLBW baby in respect of early weight gain and decrease morbidity, mortality and hospital stay in our set up. However, there are still insufficient evidences to recommend its routine use in VLBW babies in our country. Well-designed large randomized controlled trail of this intervention are needed.